(untitled) (Journal of Foreign Language Studies, 2025)
This article examines the origins, meanings, and functions of proper names used in the short story “Soulful People” by Russian writer A. Platonov. The author employed both historical names - those of real individuals who participated in the Battle of Sevastopol - and fictional names to express his views. Through these names, Platonov conveys profound imagery, emphasizes the symbolic significance of his characters, and highlights the central themes of the work. The interplay between historical reality and artistic imagination enables readers to gain a deeper understanding of the author’s intent and to immerse themselves in the work, which reflects the spirit of the era and its heroes.